Letter from Max Bredig to Ilse Wolfsberg, March 8, 1942 - Bredig, Max Albert (1942)
Max Bredig (1902-1977) writes to Ilse Wolfsberg to provide updates on his efforts to assist in the immigration case of her fiancé, Fritz Hochwald (1897-1968). Hochwald is currently interned in the Miranda del Ebro concentration camp in Spain.
Keywords: Bredig, Max Albert, 1902-1977; Wolfsberg, Ilse; Hochwald, Fritz G., 1897-1968; Miranda de Ebro (Concentration camp)